Mosquito Control Impoundments - Jorge R. Rey; C. Roxanne Rutledge Connelly (EDIS)
A mosquito control impoundment is a salt marsh or mangrove forest with an earthen dike around the perimeter that allows the area to be artificially flooded during the mosquito breeding season. Since the seventies, research has shown that impounding can have severe environmental impacts on the marshes and the adjoining estuary. So, over 12,600 hectares of the original 16,185 of impoundments have been rehabilitated in some fashion. This revised 6-page fact sheet was written by Jorge R. Rey and C. Roxanne Connelly, and published by the UF Department of Entomology and Nematology, June 2012.